2018
DOI: 10.1038/s41598-018-30449-y
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes induces fibrotic changes in the lung through the activation of TGF-β signaling pathways

Abstract: In the long term, diabetes profoundly affects multiple organs, such as the kidney, heart, brain, liver, and eyes. The gradual loss of function in these vital organs contributes to mortality. Nonetheless, the effects of diabetes on the lung tissue are not well understood. Clinical and experimental data from our studies revealed that diabetes induces inflammatory and fibrotic changes in the lung. These changes were mediated by TGF-β-activated epithelial-to-mesenchymal transition (EMT) signaling pathways. Our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 44 publications
(44 reference statements)
8
59
0
Order By: Relevance
“…This suggests that cells under exposure to high glucose concentration for prolonged times undergoes transformation and SIRT3 acts as a proliferative marker for the same. This study further confirms the results of the previous studies [38,39] which suggests that long-term diabetic condition leads to lung cancer [40]. Zhang et al have shown the involvement of SIRT3 in tamoxifen (Tam) sensitivity in breast cancer.…”
Section: Importance Of Sirt3 As a Mitochondrial Switchsupporting
confidence: 92%
“…This suggests that cells under exposure to high glucose concentration for prolonged times undergoes transformation and SIRT3 acts as a proliferative marker for the same. This study further confirms the results of the previous studies [38,39] which suggests that long-term diabetic condition leads to lung cancer [40]. Zhang et al have shown the involvement of SIRT3 in tamoxifen (Tam) sensitivity in breast cancer.…”
Section: Importance Of Sirt3 As a Mitochondrial Switchsupporting
confidence: 92%
“…Many previous studies have demonstrated that sustained hyperglycemia caused fibrotic changes in multiple organs, such as the kidney, heart, skin, and liver. A few other studies have also used a diabetic rat model to study the impact of hyperglycemia on fibrotic changes in the lung [11,46,47]. Lung fibrosis is caused by abnormal proliferation of myofibroblasts and fibroblasts, which secrete excessive ECM proteins including fibronectin, laminin, and collagens [48].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a chronic metabolic disease characterized by persistent blood hyperglycemia; it causes profound long-term effects on a variety of organs, such as the kidneys, heart, brain, eyes, and liver [1][2][3][4][5]. In recent years, increasing evidence suggests that the lung is also one of the target organs for diabetic microangiopathy with DM [6][7][8][9][10][11]. With the steady increase in the incidence of diabetes in an aging population, more and more pulmonary dysfunction is likely to be attributed to diabetic pulmonary complications [12], but few studies have addressed the role of diabetic lung injury and its therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpressions of Sirt inhibit the oxidative stress, pro-inflammatory cytokines IL-1β and p21 expressions, TGF-β1/Smad3 signaling pathway and mitochondrial DNA damage, elucidating a potential therapeutic approach to IPF. Oppositely, Talakatta observed an EMT and up-regulation of N-cadherin, Sirt3, and Sirt7 levels in diabetic cells exposed to high concentration of glucose (43), indicating that more studies should be carried out to demonstrate the exact role of Sirt on diabetic pulmonary fibrosis.…”
Section: Sirtuins (Sirt)mentioning
confidence: 99%